Звезда: [сборник] / Э.Г. Казакевич - Казакевич Э. Г. (Мировая классика, 2004)
Экземпляры: ф.16 (2004) / Инвентарный номер: 48139 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: К 14 / ГРНТИ: 17.82.82 / ББК: 84(2Рос=Рус)6-44